Effect of Intravenous Ferric Carboxymaltose on Exercise Capacity After Kidney Transplantation (EFFECT-KTx): rationale and study protocol for a double-blind, randomised, placebo-controlled trial - Arjan D van Zuilen; Stefan P Berger; Wayel H Abdulahad; Michele F Eisenga; Jacoba M Spikman; Martin H de Borst; P van der Meer; Carlo A J M Gaillard; Stephan JL Bakker; Joanna SJ Vinke; Jan-Stephan F Sanders (BMJ Open, 2023)
Introduction Iron deficiency (ID) is common and has been associated with an excess mortality risk in kidney transplant recipients (KTRs). In patients with chronic heart failure and ID, intravenous iron improves exercise capacity and quality of life. Whether these beneficial effects also occur in KTRs is unknown. The main objective of this trial is to address whether intravenous iron improves exercise tolerance in iron-deficient KTRs.Methods and analysis The Effect of Ferric Carboxymaltose on Exercise Capacity after Kidney Transplantation study is a multicentre, double-blind, randomised, placebo-controlled clinical trial that will include 158 iron-deficient KTRs. ID is defined as plasma ferritin <100 µg/L or plasma ferritin 100–299 µg/L with transferrin saturation <20%. Patients are randomised to receive 10 mL of ferric carboxymaltose (50 mg Fe3+/mL, intravenously) or placebo (0.9% sodium chloride solution) every 6 weeks, four dosages in total. The primary endpoint is change in exercise capacity, as quantified by the 6 min walk test, between the first study visit and the end of follow-up, 24 weeks later. Secondary endpoints include changes in haemoglobin levels and iron status, quality of life, systolic and diastolic heart function, skeletal muscle strength, bone and mineral parameters, neurocognitive function and safety endpoints. Tertiary (explorative) outcomes are changes in gut microbiota and lymphocyte proliferation and function.Ethics and dissemination The protocol of this study has been approved by the medical ethical committee of the University Medical Centre Groningen (METc 2018/482;) and is being conducted in accordance with the principles of the Declaration of Helsinki, the Standard Protocol Items: Recommendations for Interventional Trials checklist and the Good Clinical Practice guidelines provided by the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use. Study results will be disseminated through publications in peer-reviewed journals and conference presentations.Trial registration number NCT03769441.